Context-Specific Impact Of Antimicrobial Stewardship On Antibiotic Use And Antibiotic Resistance In Hospitals In A Lower-Middle Income Country - Results From Implementation Study With A Controlled Interrupted Time Series Design In Vietnam - Trang Quynh Le; Dung Tien Viet Vu; Quang Minh Le; Huyen Thi Thu Nguyen; Vinh Hai Vu; Duc Minh Chau; Em Thi Hoang Dung Vo; Tu Thi Cam Nguyen; Quan Anh Truong; Khanh Hong Nguyen; Hoa Nguyen Minh Le; Thomas Kesteman; et al. (Journal of Global Antimicrobial Resistance)
AIM: We aim to identify the impact of an antimicrobial stewardship (AMS) intervention, which includes pharmacist-led prospective audit with feedback, on hospital antibiotic use and resistance in two provincial-level general hospitals in Vietnam. BACKGROUND: Quality evidence on the impact of AMS is limited in Asia and often lacks of control group, resulting in biased outcomes. METHODS: We performed interrupted time-series (ITS) and controlled ITS (CITS) analyses to evaluate the impact of AMS intervention on antibiotic use in days of therapy per 1000 patient-days (DOT1000) and antibiotic non-susceptibility (NS) among hospital-acquired isolates. In each hospital, four wards received the intervention and four wards served as controls. Pre-intervention periods spanned from January 2019 to May 2020 (hospital 1) and June 2020 (hospital 2), followed by a 12-month post-intervention period (Figure 1). RESULTS: In hospital 1, a consistent significant reduction in average DOT1000 by 95.9 (CITS 95%CI [10.9, 180.8]) was observed; although both models showed inconsistent effects on slope. In hospital 2, DOT1000 showed inconsistent patterns on both level and slope. Both hospitals show inconsistent impact on AMR, particularly hospital 2 showed a reduction in average in antibiotic NS among Klebsiella spp. to ciprofloxacin, slopes in P. aeruginosa to carbapenem and ciprofloxacin. In contrast, hospital 1 have increasing level in Klebsiella spp. NS to carbapenems (Figure 2). CONCLUSIONS: The AMS impact varied between two hospitals, highlighting the context-specific implementation challenges and the need to monitor antibiotic use and resistance patterns over time to tailor interventions to the local context.